2023
DOI: 10.3390/s23115295
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Research on the Construction and Application of Knowledge Graphs for Aircraft Fault Diagnosis

Abstract: Fault diagnosis is crucial for repairing aircraft and ensuring their proper functioning. However, with the higher complexity of aircraft, some traditional diagnosis methods that rely on experience are becoming less effective. Therefore, this paper explores the construction and application of an aircraft fault knowledge graph to improve the efficiency of fault diagnosis for maintenance engineers. Firstly, this paper analyzes the knowledge elements required for aircraft fault diagnosis, and defines a schema laye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Additionally, Wu [ 29 ] utilized the BERT-BiLSTM-CRF algorithm for entity relationship extraction within the aero-engine lubrication system, subsequently constructing a fault knowledge graph for this system. Tang [ 30 ] employed deep learning as the primary method and heuristic rules as an auxiliary method to extract fault knowledge from both structured and unstructured fault data, leading to the construction of a fault knowledge graph for a specific type of process. Furthermore, Meng [ 31 , 32 ] presented a method for constructing a fault knowledge graph for aircraft power system health management and developed an intelligent Q&A system based on this knowledge graph, resulting in a significant enhancement of maintenance personnel’s troubleshooting abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Wu [ 29 ] utilized the BERT-BiLSTM-CRF algorithm for entity relationship extraction within the aero-engine lubrication system, subsequently constructing a fault knowledge graph for this system. Tang [ 30 ] employed deep learning as the primary method and heuristic rules as an auxiliary method to extract fault knowledge from both structured and unstructured fault data, leading to the construction of a fault knowledge graph for a specific type of process. Furthermore, Meng [ 31 , 32 ] presented a method for constructing a fault knowledge graph for aircraft power system health management and developed an intelligent Q&A system based on this knowledge graph, resulting in a significant enhancement of maintenance personnel’s troubleshooting abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Since Google launched the knowledge graph-based search engine in 2012, the interest in constructing and applying domain-specific knowledge graphs across industries has grown significantly. Numerous studies have confirmed the substantial application value of knowledge graph technology in various industries like electric power equipment [19][20][21][22][23][24][25][26], network communication [27][28][29][30][31], and aerospace [32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%